2015
DOI: 10.1007/s00228-015-1978-9
|View full text |Cite
|
Sign up to set email alerts
|

Cumulative incidence and risk factors of creatine kinase elevation associated with telbivudine

Abstract: The cumulative incidence of CK elevation after long-term telbivudine use is quite high, and gender and baseline eGFR may be useful predictors. However, when combined with regular monitoring of CK levels, especially for patients with lower eGFR, telbivudine is a relatively safe nucleoside analog treatment for chronic hepatitis B.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…We found that the accumulative incidence of drug resistance might increase with treatment duration, so more long-term data are needed in the future. Another concern biomarker is CK elevation during LdT therapy, which have been reported in many previous studies [16,17]. Chen, et al studied 527 CHB patients and reported that 60.91% of them had CK elevation [18], which was similar with our result (55%).…”
Section: Safety Evaluationsupporting
confidence: 91%
“…We found that the accumulative incidence of drug resistance might increase with treatment duration, so more long-term data are needed in the future. Another concern biomarker is CK elevation during LdT therapy, which have been reported in many previous studies [16,17]. Chen, et al studied 527 CHB patients and reported that 60.91% of them had CK elevation [18], which was similar with our result (55%).…”
Section: Safety Evaluationsupporting
confidence: 91%
“…A longitudinal study of muscle events associated with telbivudine found that lower baseline eGFR was a significant predictor of CK elevation in patients treated with telbivudine. 38 Based on the findings of the present study, the TIM risk tended to be higher (adjusted OR=4.82) ( Table 4 ) in patients with CKD grade 3 or higher (i.e., eGFR ≤60 mL/min/1.73 m 2 ). These data suggest that impaired baseline renal function increases the risk of telbivudine-induced myotoxicity.…”
Section: Discussionsupporting
confidence: 53%
“…Recently, Chen et al . found that male sex and lower baseline estimated glomerular filtration rate were significant risk factors for elevation of CK levels during telbivudine treatment [ 13 ]. In our patient, the CK level was markedly elevated (peak at 8050 U/L).…”
Section: Discussionmentioning
confidence: 99%